A prospective study of benign fasciculation syndrome and anxiety. Issue 6 (11th September 2018) - Filippakis, Alexandra; Jara, Jordan; Ventura, Nicholas; Scala, Stephanie; Scopa, Caitlin; Ruthazer, Robin; Karakis, Ioannis; Srinivasan, Jayashri; Russell, James A.; Ho, Doreen T.
ABSTRACT: Introduction : Benign fasciculations are common. Despite the favorable prognosis of benign fasciculation syndrome (BFS), patients are often anxious about their symptoms. In this study, we prospectively followed 35 patients with BFS over a 24‐month period. Methods : We conducted serial questionnaires to assess anxiety, associated symptoms, and duration. Results : 71.4% of patients were men, and 34.4% were employed in the medical field. Most reported anxiety, but only 14% were anxious as measured by the Zung self‐rating anxiety scale. Fasciculations were most common in the calves and persisted in 93% of patients. Anxiety levels did not change over time. Associated symptoms (subjective weakness, sensory symptoms, and cramps) were common and resolved to varying degrees. No patients developed motor neuron disease. Discussion : BFS is a benign disorder that usually persists over time. Commonly associated symptoms include subjective weakness, sensory symptoms, and cramps. BFS is usually not associated with pathologic anxiety. Muscle Nerve 58 :852–854, 2018